Effect of Firm Characteristics on Financial Performance of Listed Commercial Banks in Kenya - Nyabaga, Rodah Mong'ina; Wepukhulu, Joshua Matanda (International Journal of Economics and Financial Issues, 2020)
A country‘s economy relies majorly on the banking sector. This study examined the effect of firm characteristics on financial performance with a focus on listed banks in the Nairobi Securities Exchange for the period from 2010 to 2018. The bank characteristics examined were: capital adequacy, leverage, asset quality and bank size. The collected data was analyzed using STATA 11 and this was basically descriptive, correlation and regression analysis. The findings depicted a significant positive effect of capital adequacy on both returns on equity (ROE) and returns on assets (ROA). The findings further indicated a significant negative effect of asset quality on ROE but an insignificant negative effect on ROA. On leverage, the findings indicated a significant positive effect on ROE and an insignificant positive effect on ROA. The findings of this study indicated that bank size has a significant positive effect on both ROE and ROA. This study concluded that capital adequacy and bank size have a significant positive effect on performance. There were mixed findings on the effect of asset quality and leverage on performance. The study recommended that, listed commercial banks should maintain a considerable capital adequacy to be able to effectively absorb losses emanating from economic shocks. Keywords: Firm characteristics, financial performance, Commercial banks JEL Classifications: G2, G3 DOI: https://doi.org/10.32479/ijefi.9692